2007
DOI: 10.1074/jbc.m610464200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Apoptosis and Differentiation by p53 in Human Embryonic Stem Cells

Abstract: The essentially infinite expansion potential and pluripotency of human embryonic stem cells (hESCs) makes them attractive for cell-based therapeutics. In contrast to mouse embryonic stem cells (mESCs), hESCs normally undergo high rates of spontaneous apoptosis and differentiation, making them difficult to maintain in culture. Here we demonstrate that p53 protein accumulates in apoptotic hESCs induced by agents that damage DNA. However, despite the accumulation of p53, it nevertheless fails to activate the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
234
6
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(262 citation statements)
references
References 62 publications
21
234
6
1
Order By: Relevance
“…Our model clearly and principally differs from that of Qin et al (2007) and this may be a reason for this discrepancy. Qin et al induced p53 with UV, which caused within 6 h a significant increase of transcriptionally inactive p53 (and therefore there was no upregulation of p21 or hdm2) and downregulation of both OCT4 and NANOG at the transcriptional level.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Our model clearly and principally differs from that of Qin et al (2007) and this may be a reason for this discrepancy. Qin et al induced p53 with UV, which caused within 6 h a significant increase of transcriptionally inactive p53 (and therefore there was no upregulation of p21 or hdm2) and downregulation of both OCT4 and NANOG at the transcriptional level.…”
Section: Discussioncontrasting
confidence: 72%
“…Recently, Qin et al (2007) suggested that p53 could directly downregulate the expression of OCT4 transcription, which is important for retaining human stem cell pluripotency. Similarly, it has been shown that in mouse ESCs, p53 may bind to Nanog promoter and therefore inhibit its transcription (Lin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, no such cell cycle block was noted in a previous study of UVC-irradiated hESCs; rather, massive cell death under DNA-damaging conditions was observed [29]. However, as this study did not use synchronized hESCs and did not focus on cell cycle regulation, rigorous comparisons to our data are difficult.…”
Section: For the Experimental Design) (D-f)contrasting
confidence: 65%
“…The function of p53-p21 axis has been studied by several groups in both mouse and human ESCs and in pluripotent human embryonal carcinoma cells using various strategies [10,[29][30][31][32]. Surprisingly, there have been many discrepancies between their findings, including differences in the ability of cells to transactivate the p21 gene or to produce increased levels of p21 protein when p21 transcripts are upregulated [10,[29][30][31]33]. When we examined p53 expression in hESCs with UVC-induced G1 delay, we found that at 3 hours after UVC irradiation, p53 protein is already dramatically increased, is phosphorylated on serines 15, 33, and 392, and localizes completely to cell nuclei.…”
Section: For the Experimental Design) (D-f)mentioning
confidence: 99%
“…We also used the p53 staining protocol that worked in regular tissue to stain irradiated mammospheres and we did not get typical nucleus staining. It is reported that ES cells could not activate p53-dependent stress response and that the p53 protein in ES cells were cytoplasmic and translocated ineffectively into nucleus 21,22 . It is possible that similar mechanism may exist in the mammary stem/progenitor cells to protect the body from losing the cells to DNA damage.…”
Section: Resultsmentioning
confidence: 99%